Efektivitas Media Board Game Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Ismah Nurialsa Putri; Nur Fajri (Peneliti.net, 2023)
This research is a type of developmental research and also research and development (R&D). Research and Development aims to develop new and natural products in the innovation of a product that is already valid and can be relied upon. In this research, the product that was developed in this research was medial learning in the form of a ballroom board to improve communication skills through learning activities and thematic learning in Dalsalr School. The research subjects included students in the Tigal class of SD Negeri 1 Grobogal, which consisted of 25 students. The research design used in this study was the AlDDIE model developed by Reiser and Mollendal which was originally used as a balance in return to learning in an effective, dynamic training program infrastructure.